2017
DOI: 10.1111/ajt.14266
|View full text |Cite
|
Sign up to set email alerts
|

Novel Application of Localized Nanodelivery of Anti–Interleukin-6 Protects Organ Transplant From Ischemia–Reperfusion Injuries

Abstract: Ischemia reperfusion injury (IRI) evokes intra-graft inflammatory responses, which markedly augment alloimmune responses against the graft. Understanding the mechanisms underlying these responses is fundamental to develop therapeutic regimens to prevent/ameliorate organ IRI. Here, we demonstrate that IRI results in a marked increase in mitochondrial damage and autophagy in dendritic cells (DC). While autophagy is a survival mechanism for ischemic DC, it also augments their production of IL6. Allograft derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 65 publications
1
38
0
Order By: Relevance
“…DCs are highly specialized to absorb oxidative stress signals and increase alloimmune activation via multiple routes including enhanced expression of MHC class II and positive costimulatory molecules, and the secretion of inflammatory cytokines 19 . Our group has previously shown that ischemic dendritic cells increase IL-6 production via activation of autophagy pathways 48 and ischemic allografts from mice lacking autophagy-related gene-5 in DCs had a marked reduction in IL-6 expression 48 . Furthermore, in vitro , IL-6 production by ischemic DCs leads to increased proliferation and pro-inflammatory cytokine production by allospecific CD4 + T cells 16 , 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DCs are highly specialized to absorb oxidative stress signals and increase alloimmune activation via multiple routes including enhanced expression of MHC class II and positive costimulatory molecules, and the secretion of inflammatory cytokines 19 . Our group has previously shown that ischemic dendritic cells increase IL-6 production via activation of autophagy pathways 48 and ischemic allografts from mice lacking autophagy-related gene-5 in DCs had a marked reduction in IL-6 expression 48 . Furthermore, in vitro , IL-6 production by ischemic DCs leads to increased proliferation and pro-inflammatory cytokine production by allospecific CD4 + T cells 16 , 18 .…”
Section: Discussionmentioning
confidence: 99%
“…However, CTLA4Ig treatment has been complicated by an increased rate of early acute rejection episodes 69 , 71 and increased alloimmune activation of ischemic organs could increase the risk of rejection in CTLA4Ig treated patients. While we have previously shown the utility of anti-IL-6 in a class II mismatch model, here, we used a more clinically relevant, full MHC mismatch model of prolonged ischemia, where we investigated the synergistic effects of anti-IL-6 with CTLA4Ig 72 . Our data indicate a significant decrease in heart graft survival following severe IRI in sCTLA4Ig treated recipients, and adding anti-IL-6 abrogates this effect, by alleviating inflammation, decreasing immune cell trafficking to the ischemic organ and decreasing vascular injury; resulting in similar graft survival as control non-ischemic grafts.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence highlights the importance of novel strategies that can reduce intra-graft inflammatory responses effectively 13,14 . Intra-graft inflammatory responses have increasingly received attention as an instigator of the alloimmune response 1519 .…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these data support the use of rapamycin encapsulated as a targeted nanotherapeutic micelle to abrogate transplant fibrosis and vasculopathy when used as a donor organ preservation pre-treatment strategy. In a recent study by Solhjou et al , novel controlled-release IL-6-containing nanoparticles were utilized as a pre-treatment method in experimental cardiac allografts to blunt early IRI injury and chronic rejection responses 31. In the novel studies presented here, we approach the problem of vasculopathy in a similar fashion in the preservation phase of transplantation prior to implantation of the allograft.…”
Section: Discussionmentioning
confidence: 99%